Development of Bakas Tourism Village in Improving Local Community Income After Covid-19 Pandemic Supports G20 Agenda - Rahman, A. Faidlal; Latif, B. Syarifuddin; Clarita, Cica; H Demolingo, Ramang (Jurnal Toursci, 2024)
This research is located in Bakas Tourism Village, which is in Banjarangkan subdistrict, Klungkung Regency, Bali. Since the COVID-19 virus outbreak hit, Indonesian tourism has experienced paralysis, including the island of Bali, one of which is Bakas Tourism Village, which has resulted in a decline in local people's income. This research was conducted to analyze the development strategy of Bakas Tourism Village in increasing local community income after the COVID-19 pandemic. This study begins with an introduction to the village's potential and then continues with developing a development strategy to be used as tour packages. This study uses qualitative methods and SWOT analysis. Observation, interviews, and field documentation were carried out using data collection techniques. The results show that the potential of Bakas Tourism Village is found in natural and artificial resources, supporting facilities and infrastructure, and accessibility, which is still in the development stage. Based on the analysis that has been done, it is known that the development strategy refers to the 4A elements (Attraction, Amenities, Access, and Ancillary). The strategy carried out by POKDARWIS (Tourism Awareness Group) is to develop the potential of the western and eastern regions of the village and build cooperation with several institutions to develop village potential.